Effect of pre hot corrosion on high cycle fatigue behavior of the superalloy IN718 at 600 °C - Pradhan D.; Mahobia G.S.; Chattopadhyay K.; Singh V. (My University, 2025)
High cycle fatigue behavior of the superalloy IN718 was studied in the air at 600 °C in fully reversed stress controlled mode (R = −1), in the as heat treated condition as well as pre hot corroded in the salt mixture of 75Na2SO4 + 15NaCl + 10V2O5 (wt.%) at 600 °C for 100 h. Fatigue life of the pre hot corroded specimens was drastically reduced at all the stress amplitudes studied. The variation of fatigue life with stress amplitude followed the Basquin relationship. The endurance limit of pre hot corroded specimens was reduced by 100 MPa in respect of that of the as heat treated sample. The reduction in fatigue life was found to be associated with pits formed on the surface due to evaporation of chlorides, from the prior hot corrosion in the above salt mixture, which led to early fatigue crack initiation and rapid crack propagation. © 2018 Elsevier Ltd